2010
DOI: 10.1007/s10549-010-0863-6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of two ERCC2 (XPD) polymorphisms, Asp312Asn and Lys751Gln, in breast cancer

Abstract: The excision repair cross-complementing group 2 gene (ERCC2) plays a key role in DNA repair. Several polymorphisms in the ERCC2 gene have been described, including the commonly occurring Lys751Gln and Asp312Asn polymorphisms. Studies investigating the association of these polymorphisms with breast cancer risk produced controversial results. To evaluate these associations presented in diverse populations, we have conducted a meta-analysis based on 40 studies from 33 publications in PubMed which included analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 69 publications
3
21
0
Order By: Relevance
“…However, the published results have been contradictory. Recently, one meta-analysis study revealed no association between both polymorphisms and breast cancer risk (Pabalan et al, 2010). We had also reported similar results previously (Silva et al, 2006a).…”
Section: Nucleotide Excision Repair and Breast Cancersupporting
confidence: 89%
See 1 more Smart Citation
“…However, the published results have been contradictory. Recently, one meta-analysis study revealed no association between both polymorphisms and breast cancer risk (Pabalan et al, 2010). We had also reported similar results previously (Silva et al, 2006a).…”
Section: Nucleotide Excision Repair and Breast Cancersupporting
confidence: 89%
“…These genes are usually involved in the metabolism of environmental carcinogens, in the repair of DNA lesions induced by exogenous and endogenous carcinogens, and in the control of the cell cycle. Individual polymorphic forms in those genes have been associated with individual susceptibility to different types of cancer namely in breast and thyroid cancer (Conde et al, 2009;Gaspar et al, 2004;Pabalan et al, 2010;Peng et al, 2011;Silva et al, 2005;Silva et al, 2006b;Silva et al, 2006a;Silva et al, 2009;Silva et al, 2010;Silva et al, 2007). Several enzymes have evolved for the detoxification of xenobiotic compounds, and their gene expression is induced in response to the presence of numerous compounds (e.g., polycyclic aromatic hydrocarbons found in tobacco smoke).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous meta-analyses have been performed to investigate the association between XPD polymorphism and the risk of different types of cancer, e.g., prostate (30-32), lung (33-35), gastric (8,36), breast (7,37,38), head and neck (39,40) and Gln polymorphism-negative hepatitis B virus infection interaction in the dominant model (Gln/Gln + Lys/Gln vs. Lys/Lys). The squares and horizontal lines correspond to the study-specific OR and 95% CI.…”
Section: Discussionmentioning
confidence: 99%
“…Several important single nucleotide polymorphisms have been identified in the XPD locus, with high variant frequencies in exon 10 (rs1799793, codon 312 G→A, Asp→Asn) and exon 23 (rs1052559, codon 751 A→C, Lys→Gln) (5). These two polymorphisms have been largely investigated in genetic epidemiological studies, and individuals with these polymorphisms exhibit a higher risk of developing different types of cancer (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Lys751Gln and Asp312Asn polymorphisms were most extensively investigated. The XPD Lys751Gln polymorphism (rs13181) in codon 751 of exon 23, an A to C substitution, results in a Lys to Gln amino acid exchange (Shen et al, 1998;Pabalan et al, 2010). And Asp312Asn polymorphism (rs1799793), a G to A substitution in codon 312 of exon 10, produces Asp to Asn amino acid exchange (Shen et al, 1998;Pabalan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%